The first principle calculation of electronic and optical properties of AlN, GaN and InN compounds under hydrostatic pressure - Berrah, S.; Abid, H.; Boukortt, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Numerical simulation based on FPLAPW calculations is applied to study the lattice parameters, bulk modulus, band energy and optical properties of the zincblende binary solids AlN, GaN, InN under hydrostatic pressure. The results obtained are in a good agreement with experimental and theoretical values.